Pendapat Orangtua tentang Penerimaan Peserta Didik Baru Berbasis Sistem Zonasi di SMA Negeri 4 Payakumbuh - Puja Ningsih; Nelfia Adi (Journal of Educational Administration and Leadership, 2022)
The purpose of this research is to find and find out information related to parents' opinions about the acceptance of new students (PPDB) based on the zoning system at SMA Negeri 4 Payakumbuh viewed from an objective, accountable, non-discriminatory and transparent perspective. This research is quantitative descriptive. In this study, the population was parents of students whose children were accepted in 2020 at SMA Negeri 4 Payakumbuh, totaling 297 people and using the Stratified Random Sampling Technique in sampling with a total of 80 people. Collecting data in this study using a questionnaire or questionnaire in the form of a Likert scale. The data analysis technique was carried out in several steps, namely, data verification, scoring each answer item, classifying and tabulating data and calculating the average (mean) answers given by respondents and then describing the data that had been processed using the criteria for the real limit of the Likert scale score. The results showed that the opinion of parents about PPDB based on the zoning system at SMA Negeri 4 Payakumbuh was in the good category, with an average score of all research indicators with a score of 4.06.